2021
DOI: 10.1007/978-3-030-86478-1_15
|View full text |Cite
|
Sign up to set email alerts
|

How Important are Small Lotic Habitats of the Western Balkans for Local Mayflies?

Abstract: Mayflies are amphibious insects which represent an important link in food and energy transfer from aquatic to terrestrial habitats. They constitute a large proportion of the aquatic ecosystems' biomass. Although our knowledge about mayfly (bio)diversity in the Balkan Peninsula is still far from complete, more extensive systematic studies have been conducted within the last decade. In this chapter we explore development of mayfly research in the area of the Western Balkans, mayfly species richness in various sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the presence or absence of mayfly species can provide important clues about the environmental health status and of the aquatic system. This enables their use as bio-indicators of the environmental conditions and helps in water quality assessments [2][3][4]. Mayfly nymphs are strongly influenced by several environmental conditions, for example, Vilenica et al [4] noted that the nymphal growth, embryonic development, and survival rate were affected by water temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the presence or absence of mayfly species can provide important clues about the environmental health status and of the aquatic system. This enables their use as bio-indicators of the environmental conditions and helps in water quality assessments [2][3][4]. Mayfly nymphs are strongly influenced by several environmental conditions, for example, Vilenica et al [4] noted that the nymphal growth, embryonic development, and survival rate were affected by water temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This enables their use as bio-indicators of the environmental conditions and helps in water quality assessments [2][3][4]. Mayfly nymphs are strongly influenced by several environmental conditions, for example, Vilenica et al [4] noted that the nymphal growth, embryonic development, and survival rate were affected by water temperature. Also other studies showed that mayflies are negatively associated with increasing conductivity and TDS of the aquatic system [5][6][7].…”
Section: Introductionmentioning
confidence: 99%